Implementation of Student Centered Learning in History Class: A Qualitative Study at SMA Lab School Untad Palu - Isnaeni Isnaeni; Nuraedah Nuraedah; Haliadi Haliadi; Minarni Nongtji (Journal of Educational Sciences, 2026)
The research investigates how Student Centered Learning (SCL) operates in history classes at SMA Lab School Untad Palu and assesses its effects on student participation and their educational experiences. The research used a qualitative descriptive research method. The research involved two history teachers and fourteen students from eleventh grade. The researchers collected data through three methods which included classroom observations and semi-structured interviews as well as documentation. The researchers analyzed the data using the Miles and Huberman interactive model which consists of three steps: data reduction and data display and conclusion drawing. The results show that SCL implementation occurred through three elements which included systematic planning and interactive classroom activities and process-based evaluation. Teachers conducted their role as facilitators by creating opportunities for students to engage in group discussions and presentations and reflective activities. The results show that students’ participation increased significantly because they developed more confidence in sharing their thoughts and working together with others. Students demonstrated two positive outcomes: they showed increased motivation and their critical thinking abilities improved. The SCL method successfully improved history learning because it created an authentic learning experience that centered on student needs despite the obstacles of time constraints and diverse student learning capabilities.